COMPLEX SCENARIO OF MEN 1 WITH ECTOPIC PARATHYROID GLAND: A CASE REPORT - Bahrudin, Mohd Fyzal; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND In the context of Multiple Endocrine Neoplasm 1 (MEN1), primary hyperparathyroidism (PHPT) is the most prevalent form of endocrinopathy and is often the earliest endocrine manifestation among patients. It represents 2–4% of all forms of PHPT. Ectopic parathyroid adenomas (EPTA) account for a significant proportion, approximately 22% of PHPT cases. To mitigate the adverse effects of PHPT in MEN1 patients, the optimal course of treatment is parathyroidectomy. We present a complex case of MEN1 that involves an ectopic parathyroid gland. CASE A 54-year-old female presented with symptomatic hypercalcemia with a serum calcium of 3.63 mmol/L (2.1-2.55) along with multiple duodenal ulcers and a Hb of 8.7g/dL (12-15) in 2008. Clinical diagnosis of Multiple Endocrine Neoplasia 1 was made, as validated by primary hyperparathyroidism, microprolactinoma and non-functioning pancreatic neuroendocrine tumour grade 1. She underwent total parathyroidectomy in July 2008 with a right inferior auto-transplantation into the sternocleidomastoid muscle. Histopathological analysis confirmed parathyroid hyperplasia in all 4 glands. Ten years later, she exhibited an increasing trend of serum calcium 2.57-2.63 mmol/L and iPTH (7.05->12.89->14.4 pmol/L) (1.58-6). Neck ultrasonography revealed a welldefined elongated hypoechoic structure within the right sternocleidomastoid muscle measuring 0.2 x 0.4 x 0.9 cm (AP x W x CC). Parathyroid scintigraphy Tc99M Sestamibi with SPECT-CT demonstrated the presence of an ectopic parathyroid adenoma measuring 0.7 x 0.9 cm at the right upper paratracheal/suprasternal region. Subsequently, she underwent exploratory parathyroidectomy with the removal of the right auto-transplant parathyroid gland and right thymus. Histopathological analysis was consistent with parathyroid hyperplasia and ectopic parathyroid accordingly. Postoperatively she remained hypercalcaemic 2.7 mmol/L with non-suppressible iPTH 27.46 pmol/L. Levels of 25-OH (D) were insufficient at 40.72 nmol/L. Further localization studies were contemplated. However, 4D CT assessment was not done due to her deteriorating renal function. She was given oral cholecalciferol 1000 IU daily and cabergoline 1 mg daily. CONCLUSION Despite significant progress in imaging technologies and surgical techniques, the management of EPTA remains a challenging task in clinical practice. Specialized multidisciplinary input is crucial in managing such cases.